2014
DOI: 10.9790/0853-131151822
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Traumatic Dental Injuries among Blind School Children in South Karnataka

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
(38 reference statements)
4
12
0
Order By: Relevance
“…Most of TDIs affect the central incisors .There were significant correlations between increased overjet and/or inadequate lip coverage and prevalence of TDIs. This is in agreement of all the studies which correlate the prevalence of TDIs and the degree of overjet and lip coverage (1,14,16,(22)(23)(24)(25) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most of TDIs affect the central incisors .There were significant correlations between increased overjet and/or inadequate lip coverage and prevalence of TDIs. This is in agreement of all the studies which correlate the prevalence of TDIs and the degree of overjet and lip coverage (1,14,16,(22)(23)(24)(25) .…”
Section: Discussionsupporting
confidence: 92%
“…In India nearly the same prevalence 34.95 % were found among 103 blind individuals (22) while it was 35.7% among 80 visually impaired children in another study (23) with Increased overjet and inadequate lip coverage being significantly associated with the occurrence of trauma in both studies.…”
Section: Introductionmentioning
confidence: 77%
“…In contrast to the findings of previous studies, 15–17,19 most of the adolescents in the current study who suffered TDIs were females. Additionally, the magnitude of the association suggests that adolescents who are blind 13,16 were twice as likely to have a TDI. However, no statistically significant difference was shown.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review, Silveira et al demonstrated that people with special needs have an increased chance of suffering dental trauma 9 . However, the prevalence of TDI in adolescents with visual impairment is not consistent and has varied between 19% and 50.6%, depending on the type of study 8,10–17 4,18,19 which can prevent or minimize sequelae and influence prognosis 4,18–21 …”
Section: Introductionmentioning
confidence: 99%
“…15 This indicates lack of awareness among parents and caretakers in visually impaired schools with regard to dental trauma. 16 This study has certain constraints. There is a need to devise a suitable system for the delivery of preventive measures.…”
Section: Ijpcdrmentioning
confidence: 99%